LEGISLACIÓN LABORAL Y NUEVAS FORMAS DE TRABAJO (2016)
The work is complex, it has many and careful dimensions: economic, legal, moral, ethic, psychologic, social and human. Work is necessary for the social and economic development. In this paper we speak about the economic and enterprise work dimensions and the relationship with the current Colombian Labor Law.